(untitled) (Research, Society and Development, 2021)
Objective: To investigate the individual and dietary characteristics of individuals undergoing treatment for gastrointestinal (TGI) cancer at a High Complexity Oncology Unit. Method: Cross-sectional, quantitative, descriptive and exploratory study, based on secondary data from a previous study that used its own questionnaire and information from medical records and the “How is your Food?” Test from the Ministry of Health, Brazil. Absolute and relative frequencies and the p-value were obtained of all included variables. Results: A total of 22 cases of TGI cancer were detected, most of them self-reported black or brown race / color, female, with partner, with up to two children, lower household density, lower education and no occupation. It was also observed higher consumption of fruits and pulses, low vegetables, meat, dairy products and carbohydrates in general, in addition to a high consumption of sweets, and fats. The practice of physical activity was low and alcoholism was high in the sample studied. Despite this, the good quality of food was more self-reported, as was the habit of four or more meals a day. Final considerations: Results that indicate the presence of individual, food and nutritional characteristics of gastrointestinal cancer in the studied group, such as high consumption of fats and sweets and low consumption of vegetables. Adequate nutritional intervention is necessary in these individuals, and they may also be followed after treatment. In summary, we highlight the role of an inadequate dietary profile, which associated with a sedentary lifestyle are risk factors for the onset of various chronic diseases, such as cancer.